2015
DOI: 10.1016/j.ijdevneu.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

ERK1, 2, and 5 expression and activation in dopaminergic brain regions during postnatal development

Abstract: Degeneration and dysfunctioning of dopaminergic neurons in the midbrain have been associated with serious neurodegenerative and neuropsychiatric disorders. Elucidating the underlying neurobiology of these neurons during early postnatal development may provide important information regarding the etiology of these disorders. Cellular signaling pathways have been shown to regulate postnatal neuronal development. Among several signaling pathways, extracellular-regulated mitogen kinases (ERK) 1, 2, and 5 have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…While others have noted increases and decreases in ERK1/2 activation following resveratrol administration in the hippocampus [12, 28], these are the first studies to examine the effects of resveratrol or pinostilbene on ERK1/2 activity in the striatum. This data complements work published by Parmar and colleagues demonstrating that ERK1/2 is important for DA cell survival [78] and possible DAergic region development [79]; therefore, the increase in the ERK1/2 by these phytochemicals could be contributing to the healthy state or functioning of DAergic neurons.…”
Section: Discussionsupporting
confidence: 90%
“…While others have noted increases and decreases in ERK1/2 activation following resveratrol administration in the hippocampus [12, 28], these are the first studies to examine the effects of resveratrol or pinostilbene on ERK1/2 activity in the striatum. This data complements work published by Parmar and colleagues demonstrating that ERK1/2 is important for DA cell survival [78] and possible DAergic region development [79]; therefore, the increase in the ERK1/2 by these phytochemicals could be contributing to the healthy state or functioning of DAergic neurons.…”
Section: Discussionsupporting
confidence: 90%
“…The MAPK family is an important signaling pathway of Nox2-derived ROS involved in many brain physiological and pathological processes, including maintenance of neuronal viability, vascular alteration, and apoptosis (3437). Increased ERK1/2 expression has been found in age-related neurodegenerative abnormalities (36). In support of these previous studies, we found Nox2-dependent ERK1/2 activation together with a significant increase in brain cell DNA damage, i.e., increased γH2AX and p53, in the midbrains of aging WT mice and elderly humans.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of dopaminergic signaling plays an important role in the midbrain and frontal cortex during postnatal development [235,236]. Midbrain dopaminergic neurons in the substantia nigra pars compacta and ventral tegmental area regulate extrapyramidal movement and important cognitive functions, including motivation, habit learning, and reward associations [237].…”
Section: Appetite Control and Feeding Rewardmentioning
confidence: 99%